A Dimension Analysis of Job Satisfaction Effect on Employee Organizational Commitment - Yakup, Yakup; Paulutu, Risman; Paramata, Moh Rolli (Mabsya: Jurnal Manajemen Bisnis Syariah, 2021)
This study aims to analyze the dimensions of job satisfaction and its influence on employee organizational commitment at the Regional Finance Board of Pohuwato Regency. The data used in this study are primary data that comes from filling out questionnaires. The study population was 59 employees using the census method. The analysis technique used to answer research problems and test hypotheses is multiple regression analysis with the help of Statistical Product Service Solution (SPSS) software which is used to analyze the data. The results of this study are (1) there is a positive and significant effect on the satisfaction dimensions of the job itself. toward employee organizational commitment, (2) there is a positive and significant influence on the dimensions of satisfaction on salaries on employee organizational commitment, (3) there is a positive and significant influence on the dimension of satisfaction in supervision of employee organizational commitment, (4) there is a positive and significant influence on the satisfaction dimensions of employees promotion opportunities on employee organizational commitment, (5) there is a positive and significant effect of the satisfaction dimensions of coworkers on employee organizational commitment, (6) there is a positive and significant influence on the dimensions of satisfaction in working conditions on employee organizational commitment. The dominant variable that affects organizational commitment is the satisfaction dimension of promotion opportunities. The findings of this study indicate that if the dimensions of job satisfaction are increased, the organizational commitment of employees to the organization will increase.